Analysis of the Implementation of Al Farabi Academic Information System Management in Supporting the Quality of Educational Services in the Academic and Financial Fields - Misbahhudin Misbahhudin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The implementation of academic information systems in higher education institutions often encounters challenges related to management effectiveness, human resource readiness, system integration, and service quality. Similar conditions were identified in the implementation of the Al-Farabi Academic Information System (Si-Aa) at STITNU Al-Farabi Pangandaran, where efforts to improve academic and financial services still require optimization. This study aims to analyze the implementation of the managerial functions of planning, organizing, directing, and controlling in the management of Si-Aa, as well as their contribution to improving the quality of academic and financial services. This research employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, direct observation, and documentation. The analysis focused on the implementation of the four core management functions in Si-Aa management and utilized the SERVQUAL model to assess the quality of academic and financial services provided to students and other academic stakeholders. The findings indicate that the implementation of Si-Aa management has generally contributed positively to improving service quality by enhancing efficiency, transparency, and accountability. However, several challenges remain, including limited technical training for system operators and suboptimal data integration across institutional units. The successful implementation of Si-Aa is supported by leadership commitment, adequate technological infrastructure, and effective communication among organizational units. The originality of this study lies in its integration of managerial functions with Islamic values and the local institutional context, offering a contextual model for managing academic information systems in Islamic higher education institutions. Since this study is limited to a single institution, the findings cannot be generalized to other higher education settings. Future studies are recommended to employ quantitative methods or comparative approaches involving multiple institutions to strengthen the generalizability of the findings.